Peluang Pengembangan Kedelai pada Areal Pertanaman Ubi Kayu di Lahan Kering Masam - Arief Harsono; Subandi Subandi (Iptek Tanaman Pangan, 2013)
Cassava crop occupies the largest land area among the food crops in the acid soil drylands. Farmers tend to grow cassava as a monocrop, so that farmers’ income derived solely from cassava only. Intercopping of cassava + soybean following the cropping pattern of cassava + soybean/+ goundnut or cassava + groundnut /+ soybean, could improve farmers’ income derived from the soybean and groundnut crops, without reducing the cassava tuber yield. Technology to improve soil productivity for such cropping pattern is available, consisting of soil amelioration using dolomite, high nutrient organic fertilizer “Santap-M” rhizobium innoculation “Illetrisoy stain” and inorganic fertilizer. The cropping pattern is considered suitable for improving soil fertility on cassava planted area.